2022
DOI: 10.3168/jds.2021-21068
|View full text |Cite
|
Sign up to set email alerts
|

Lactational performance of dairy cows in response to supplementing N-acetyl-l-methionine as source of rumen-protected methionine

Abstract: The objective of this experiment was to evaluate the effects of supplementing a rumen-protected source of Met, N-acetyl-l-methionine (NALM), on lactational performance and nitrogen metabolism in early-to midlactation dairy cows. Sixty multiparous Holstein dairy cows in early lactation (27 ± 4.3 d in milk, SD) were assigned to 4 treatments in a randomized complete block design. Cows were blocked by actual milk yield. Treatments were as follows: (1) no NALM (control);(2) 15 g/d of NALM (NALM15); (3) 30 g/d of NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
3
6
0
Order By: Relevance
“…The difference between adding different RPM contents could be ignored. The results showed that adding RPM to the diet did not significantly improve the milk yield of the dairy cows, which was consistent with the research results of some scholars [ 2 , 5 ], Although the dairy NRC (2001) pointed out that adding RPL or RPM can improve milk yield, which is likely to be achieved by improving the efficiency of the MP in milk protein synthesis, there are also reports that adding methionine + lysine can improve the milk yield more than providing only one AA [ 24 , 25 , 26 ]. As for the results for the milk composition index, adding RPM to the diets of dairy cows can significantly improve the milk fat rate and milk protein rate.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The difference between adding different RPM contents could be ignored. The results showed that adding RPM to the diet did not significantly improve the milk yield of the dairy cows, which was consistent with the research results of some scholars [ 2 , 5 ], Although the dairy NRC (2001) pointed out that adding RPL or RPM can improve milk yield, which is likely to be achieved by improving the efficiency of the MP in milk protein synthesis, there are also reports that adding methionine + lysine can improve the milk yield more than providing only one AA [ 24 , 25 , 26 ]. As for the results for the milk composition index, adding RPM to the diets of dairy cows can significantly improve the milk fat rate and milk protein rate.…”
Section: Discussionsupporting
confidence: 90%
“…The retrieved studies were screened according to the corresponding inclusion criteria. After excluding the duplicate and unqualified literature, the meta-analysis included 14 studies, as shown in Table 1 [ 1 , 2 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. To make it easier to visualize the studied datasets, the mean, maximum, minimum, and standard deviation of each study parameter are summarized in Table A1 of Appendix A .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al (2019) reported that NALM supplemented at rates of 0, 15, 30, and 60 g/day to mid-lactation dairy cows improved milk yield in a quadratic manner, with 30 g/day of NALM seeming to be the optimal supplementation rate for milk yield under the experimental conditions. Amaro et al (2022) found that milk yield of early lactating Holstein dairy was not altered by three different supplementation rates (15, 30, and 45 g/day) of NALM compared to control animals.…”
Section: Discussionmentioning
confidence: 84%
“…Supplementation of the Met derivative increased milk fat concentration and yield (Fagundes et al, 2018), whereas supplementation of NALM to early and mid‐lactation dairy cows improved milk yield (Liang et al, 2019) and 3.5% fat‐corrected milk/dry matter intake (DMI; Amaro et al, 2022). All three studies exhibited the greatest lactational performance and feed efficiency when NALM was supplemented in lactation diets at 30 g/day (Amaro et al, 2022; Fagundes et al, 2018; Liang et al, 2019). The NALM is a Met derivative produced by chemical protection of the L‐Met α‐amino group with a N‐acetyl group.…”
Section: Introductionmentioning
confidence: 99%